Chemical composition, degradability, and in vitro gas production of foliage from twelve sweet potato cultivars (Ipomoea batatas Lam) - Ojeda, A.; Matos, A. A.; Cardozo, A. R. (Cuban Journal of Agricultural Science, 2013)
An experiment was performed to assess the chemical composition, the in vitro degradability of the dry matter at 48 and 96 h (Deg48 and Deg49, respectively), the accumulated gas production at 48 and 96 h (Gas48 and Gas96, respectively), and to estimate the metabolizable energy (ME) of the foliage of twelve cultivars of sweet potato (Ipomoea batatas Lam). They were identified as Huambanchero, Mariara, Topera, Tucutunemo, DLP2850, FNC765, 15, 21, 44, 45, 60, and 199069.1, and they were cultivated for 120 d in seven blocks, each of 12 plots (21.6 m2). There were not differences in the chemical composition (11.5 ? 1.3 % CP, 3.6 ? 0.2 % SE, 40.8 ? 3.2 % NDF, 15.1 ? 1.5 % ashes, 1.3 ? 0.3 % Ca, and 0.56 ? 0.1 % P), Gas48 and Gas96 (216.5 ? 8.1 and 281.0 ? 18.5 mL, respectively), fractional rate of gas production (0.06 ? 0.004 mL/h), and phase of delay (2.7 ? 0.24 h). The Mariara cultivar had the highest (P < 0.01) Deg48 and ME (84.8 % and 13.7 MJ/kg MS, respectively), whereas the lowest records corresponded to Huambanchero (72.1 % and 12.7 MJ/kg DM, respectively). The Deg48 had positive correlations (r=0.99, P < 0.01) with Gas96, the fractional rate of gas production, the phase of delay, and the ME. It is concluded that the foliage of sweet potato from the cultivars under study is a fibrous material with chemical composition, parameters of rumen fermentation, in vitro degradability, and ME suggesting its use as alternative resource for the feeding of ruminants in the tropics. Key words: Ipomoea batatas, foliage, metabolizable energy, feeding, ruminants, tropics.